Pemanfaatan Limbah Hasil Pembakaran Batubara Faba (Fly Ash dan Bottom Ash) PLTU Menjadi Paving Block - Dian Isnandar; Harjuni Hasan; Albertus Juvensius Pontus; Agus Winarno; Windhu Nugroho (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Water absorption test and compressive strength test were conducted to determine the quality standards of paving blocks. This research was conducted by using a mixture of fly ash, bottom ash and cement. The tests carried out in this study were water absorption test and compressive strength test using 3 compositions of 5%, 8% and 12%. In each composition using 3 samples for testing. Tests were carried out with a vulnerable time between 7 days, 14 days and 28 days. The highest water absorption results in the 8% composition with water absorption of 1.467%. The highest compressive strength results in the 8% composition with a compressive strength of 10.479 Mpa.